von Willebrand Disease in a Pediatric-based Population - Comparison of Type 1 Diagnostic Criteria and Use of the PFA-100® and a von Willebrand Factor/Collagen-binding Assay - Dean, J.A.; Blanchette, V. S.; Carcao, M. D.; Stain, A. M.; Sparling, C. R.; Siekmann, J.; Turecek, P. L.; Lillicrap, D.; Rand, M. L. (Thrombosis and Haemostasis, 2000)
Definitive diagnosis of type 1 von Willebrand Disease (VWD) remains a problem. Provisional consensus guidelines for the diagnosis of definite and possible type 1 VWD were prepared by the Scientific Subcommittee on von Willebrand factor (VWF) of the Scientific and Standardization Committee (SSC) of the International Society on Thrombosis and Haemostasis (ISTH) during the 1996 annual meeting for the specific purpose of further evaluation in retrospective and prospective studies by a Working Party on Diagnostic Criteria (1996 Annual Report of the SSC/ISTH Subcommittee on VWF). In the first phase of this study, we compared 2 definitions of type 1 VWD, each with 3 criteria: significant bleeding history, laboratory investigations, and family history. Using the ISTH consensus guidelines for type 1 VWD definition, significantly fewer patients were diagnosed with definite type 1 disease as compared to our “in house” Hospital for Sick Children (HSC) criteria (4 vs. 31). While we recognize that the provisional ISTH consensus guidelines were not intended for clinical use, we believe that the results of our studies are of interest and will assist in any future refinements to the ISTH guidelines.In the second phase of this study, we investigated the utility of 2 new tests, a laboratory screening test and a functional test, for VWD in our well characterized, pediatric-based population. The Platelet Function Analyzer (PFA-100®) provides an in vitro measure of primary hemostasis under conditions of high shear, using disposable cartridges containing collagen and either epinephrine or ADP. All tested subjects with types 2 or 3 VWD had prolonged PFA-100 closure times (CTs) with both cartridge types (n = 17) and prolonged bleeding times (n = 14). In subjects with definite type 1 VWD, 20/24 (83%) had prolonged CTs with the collagen/ADP cartridge (19/24 (79%) with collagen/epinephrine), compared with 7/26 (27%) with prolonged bleeding times. In subjects with definite types 1, 2, or 3 VWD, collagen/ADP CTs were abnormal in 37/41 subjects, giving an overall sensitivity of 90%. With this high sensitivity, the PFA-100 is a better screening test for VWD than the bleeding time.We also tested a VWF collagen-binding assay (VWF:CBA) as a functional test for VWF, in comparison with the more routinely-used ristocetin cofactor assay (VWF:RCo). The VWF:CBA is based on an ELISA technique, which has the potential to be more reproducible than the VWF:RCo. We found that the VWF:CBA detected 43/49 (88%) subjects with definite types 1, 2, or 3 VWD, performing as well as the VWF:RCo, that detected 42/48 (88%). We also showed that, used in conjunction with VWF antigen levels, the VWF:CBA may be useful in classification of VWD subtypes.
Keywords: von Willebrand disease; pediatrics; PFA-100; collagen-binding activity; type 1 von Willebrand disease